Diseño de una planta procesadora de lácteos para el contón chambo, provincia de Chimborazo - Pérez Rosero, María José (2011)
Chambo town is a highly productive beef cattle to dairy and a total production of 25,200 liters / day, creating the need for the design of a dairy plant in Canton. This project is based on research deductive, inductive, dialectical, whose level is descriptive research, and observation as a methodological technique. All study serves to reveal the assumptions that later could be considered as the most feasible and valid to investigate and verify the reality of life by providing an alternative socio - economic for the population at the time of project implementation, taking into consideration that must be accommodate the study design in terms of infrastructure, machinery, work areas, personal development, recommendations for strategic environmental impact activities and locations in their area.